Do two South American species of Cheilanthes (Pteridaceae) traditionally linked to the Cheilanthes marginata group, belong to Gaga? - Ponce, Monica; Scataglini, Maria Amalia (Phytotaxa, 2016)
The phylogenetic positions of Cheilanthes hieronymi and C. poeppigiana are tested using DNA sequences of plastid matK and rbcL markers. These South American species are historically linked to Cheilanthes marginata, now transferred to the new genus Gaga. The results showed that C. hieronymi  and C. poeppigiana are located outside Gaga. The study corroborated that the morphological similarities between the two species and the genus Gaga were resulted from convergences.